THE USE OF AI TOOLS TO CREATE STEM PRESENTATIONS: A COMPARATIVE STUDY - YSMAEL CENAS CHACON, FERNANDO (2024)
AI IS ONE OF THE TOOLS THAT IS MAKING ITS WAY INTO UNIVERSITY EDUCATION DUE TO THE INFINITE NUMBER OF POSSIBILITIES IT HAS GENERATED SINCE ITS APPEARANCE, IN THIS SENSE, THIS STUDY WAS CONDUCTED WITH THE OBJECTIVE OF DESCRIBING THE EXPERIENCES ACHIEVED BY UNIVERSITY STUDENTS ON THE USE OF AI FOR THE CREATION OF PRESENTATIONS THAT ENRICH THEIR KNOWLEDGE IN THE DISCIPLINARY AREAS OF PHYSICS, MATHEMATICS AND CHEMISTRY. DATA WERE COLLECTED USING A LIKERT-TYPE QUESTIONNAIRE CONSISTING OF FIVE (5) RESPONSE OPTIONS, SPECIFICALLY USING GOOGLE FORMS. THE PARTICIPANTS WERE STUDENTS OF PHYSICS, MATHEMATICS AND CHEMISTRY COURSES, WITH A POPULATION OF 1,215, OF WHICH THE SAMPLE WAS 120 IN EACH OF THE COURSES. THE RESULTS SHOWED 98.3% OF STUDENTS WITH A HIGH LEVEL OF SATISFACTION EQUALLY IN ALL COURSES, 96% INDICATED THAT THE USE OF AI PROMOTES COLLABORATIVE WORK, 97.3% FELT HIGHLY MOTIVATED, WHICH OCCURRED IN THE CHEMISTRY COURSE, AND AS FOR THE IMPROVEMENT OF KNOWLEDGE AND LEVEL OF COGNITIVE DEVELOPMENT, THIS WAS 99.2% IN THE AREA OF MATHEMATICS. AS PART OF THE CONCLUSIONS, IT CAN BE MENTIONED THAT BY USING AI AS A TECHNOLOGICAL TOOL THAT SUPPORTS THE CREATION OF INTELLIGENT PRESENTATIONS IN GENERAL, IMPROVEMENT STAGES ARE REACHED IN TERMS OF SATISFACTION, MOTIVATION, COLLABORATIVE WORK AND CREATIVE WAYS OF LEARNING. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.